Influência do diabetes tipo 1 no reparo de lesões produzidas por implantes intraperitoneais e subcutâneos em ratos wistar - Teresa de Jesus Oviedo Socarras (2014)
The high prevalence of diabetes and the enormous therapeutic potential of biomedical implants to repair and/or replace biological tissues justify further investigation to determine the influence of hyperglycemia in tissue response to synthetic implants. This study investigated the effect of chemically induced type 1 diabetes in components of fibrovascular tissue (inflammation, angiogenesis, fibrogenesis and apoptosis) in subcutaneous and intraperitoneal implants of polyether polyurethane in rats. Angiogenesis, as determined by the number of vessels in fibrovascular tissue, was lower in both intraperitoneal and subcutaneous implants of diabetic animals. The level of VEGF (pro-angiogenic cytokine) did not differ in the subcutaneous implants of both groups but increased in intraperitoneal implants of diabetic animals when compared to non diabetics. Markers of fibrogenesis (fibrous capsule thickness, total collagen and TGF-1 levels) were 2-fold higher in subcutaneous implants of non diabetic animals than in diabetics. However, these markers showed no differences betweenintraperitoneal implants in diabetics and non diabetics. Some inflammatory parameters such as the activity of N-acetylglucosaminidase (NAG) and the levels of monocyte chemoattractant protein-1 (MCP-1) and TNF- were higher in intraperitoneal implants in diabetic animals than in non diabetic, but there was no difference in the accumulation of neutrophils, as determined by myeloperoxidase (MPO) activity. In subcutaneous implants, MPO, TNF-, MCP-1, mast cells and apoptosis) were increased, awhile the activity of macrophages and the number of giant cells were significantly lower in the diabetic group. It is evident that the pattern of foreign body reactions to synthetic matrix of polyether polyurethane implants differs between normoglycemic and hyperglycemic rats and also suffers the influence of the implantation site. These findings may be relevant in understanding the interaction/integration between biomaterial and tissue in the diabetic state.